SPECIAL STRATEGY OF TREATMENT OF DIFFICULTY-PROFILE CONICAL SCREW SURFACES OF SINGLE-SCREW COMPRESSORS WORKING BODIES - Vasil'ev, A. S.; Goncharov, A. A. (Zapiski Gornogo instituta (1999), 2019)
The article deals with the problems arising during the shaping of complex profile tapered helical surfaces. These surfaces form the geometry of the working bodies of single-screw miniature compressors, which have great prospects for use in mobile miniature compressor plants, which is especially important for medical and space technology, robotics, oil and gas and mining industries. Due to the fact that the capabilities of existing CAD systems do not allow obtaining three-dimensional models of these surfaces, the problem of preparing a control program for a CNC machine arises, since the calculation of the tool path in CAM systems when processing complex surfaces is impossible without a three-dimensional surface model. To solve the problem, an automated programming system was developed that implements a formalized toolpath calculation in accordance with the proposed special processing strategy for conical helical surfaces. As the initial data for calculating the toolpath, the system needs information about the tool geometry and the helical surface in a parametric form, which makes it possible to abandon the construction of a three-dimensional surface model. The results of processing prototypes for the proposed strategy are given.